2022
DOI: 10.1186/s12912-022-01114-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sleep disturbance on the association between work–family conflict and burnout in nurses: a cross-sectional study from South Korea

Abstract: Background Sleep disturbances can lead to work–family conflicts and affect the mental health of nurses. This study aimed to investigate the mediating effect of sleep disturbance on the association between work–family conflict (WFC) and burnout in nurses. Methods Responses to a questionnaire from 156 nurses working in a hospital in South Korea were analyzed. Multiple linear regression analysis and PROCESS Macro Model 4 were used to analyze the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Finally, the findings indicated that better sleep quality had a positive impact on the parent-child relationships of nurses. This may be because nurses who sleep poorly experience higher intensity workloads or more frequent night shifts, thereby reducing the time and effort invested in managing their children [ 9 , 35 ] Fujimoto et al (2008) found that three-shift duties are more likely to increase work-family conflict. Similarly, conflicts may escalate when there is a lack of support for early childhood care responsibilities in the workplace [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the findings indicated that better sleep quality had a positive impact on the parent-child relationships of nurses. This may be because nurses who sleep poorly experience higher intensity workloads or more frequent night shifts, thereby reducing the time and effort invested in managing their children [ 9 , 35 ] Fujimoto et al (2008) found that three-shift duties are more likely to increase work-family conflict. Similarly, conflicts may escalate when there is a lack of support for early childhood care responsibilities in the workplace [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria: (1) intern or refresher nurses; (2) nurses with a child under the age of two, based on the applicability of the scale and Piaget’s theory on cognitive development [ 34 , 39 ]. To ensure an appropriate sample size for the linear multiple regression analyses [ 35 ], G*power version 3.1.9.7 was used; assuming a significance level of 0.05, a median effect size of 0.15 [ 35 ], a power of 95%, and 20 predictors, the sample size was calculated to be 222 participants. Allowing for a sample loss rate of 20%, at least 278 participants needed to be surveyed.…”
Section: Methodsmentioning
confidence: 99%
“…Burnout reflects a condition of perceived failure or exhaustion caused by failure to meet the expected workload in terms of energy, strength, and resources (Efıl et al, 2022). Scholars have suggested that burnout is rooted in long-term work pressures and a lack of appropriate relief (Han & Kwak, 2022). Burnout may cause people to lack the necessary energy to work or reduce their work willingness (Nabizadeh-Gharghozar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%